Unravelling the Drivers of Digital Literacy in Indonesia’s Distance Learning Era - Kharis, Selly Anastassia Amellia; Septiarini, Tri Wijayanti; Zili, Arman Haqqi Anna; Arisanty, Melisa; Permatasari, Sri Maulidia (Universitas Muhammadiyah Mataram, 2025)
In Indonesia’s rapidly evolving distance learning landscape, digital literacy has become a critical competency for ensuring academic quality and ethical online engagement. However, existing assessments often focus narrowly on technical skills, overlooking behavioral and ethical dimensions that are equally essential in digital environments. This study aims to identify the key factors influencing digital literacy among students in Indonesia's distance learning environment, focusing on Universitas Terbuka. Utilizing a Random Forest algorithm, the research involves data preprocessing, model development and evaluation, and feature importance analysis to determine the most influential predictors. The findings reveal that digital ethics and behavioral aspects-such as academic integrity, proper citation practices, and responsible social media conduct- are the strongest indicators of digital literacy, whereas technical proficiency in e-learning platforms plays a less dominant role. This study's novel use of Machine Learning offers a methodological contribution to the assessment of digital literacy in educational settings. Based on these insights, the paper recommends a holistic approach to digital literacy education at Universitas Terbuka, advocating for programs that integrate technical training with robust digital ethics instruction, including awareness of citation, plagiarism, communication etiquette, privacy, and responsible information dissemination.